MAKTABGACHA TAʼLIM OʻQUVCHILARINI TARBIYALASHDA MILLIY QADRIYATLARNING OʻRNI (Multidisciplinary Journal of Science and Technology, 2025)
This article discusses the role and importance of national values ​​in the process of educating children of preschool age. The study analyzes folk pedagogy, national customs, traditions, values, and their role in the spiritual and moral formation of children's personalities. It also examines the pedagogical conditions, effective methods and means of integrating national values ​​into the educational process in preschool educational institutions. The article scientifically substantiates that education based on national values ​​serves to develop such qualities in children as patriotism, humanity, awareness of their national identity, and social adaptation.